The Intellectual Origins of the Global Financial Crisis - Toay, Taun N.; Berkowitz, Roger, 1968- (Book collections on Project MUSE., 2012)
"From easy money to greed, there is no shortage of explanations for the global financial crisis that began in 2008. Some even deny it is a crisis, arguing that the Great Recession is just one of the many busts that are inevitable in the boom and bust cycle that plagues capitalist economies. Yet the claim that the financial crisis is just part of capitalism is an evasion that refuses to make judgments about the individual and collective actions that helped make this particular crisis possible. This book brings together philosophers, businessmen, economists, political theorists, and historians to ask after the cultural and intellectual transformations that underlie this particular crisis. Grounded in the thinking of Hannah Arendt, the essays touch upon Max Weber, Karl Marx, Adam Smith, John Maynard Keynes, and Michel Foucault. Some essays trace the rise of economic thinking and the decline of political judgment. Others explore how Keynesian economics is either a cause or a cure of the financial crisis. And still others ask pointed questions about contemporary business practices and the culture of financial capitalism. As a whole, the volume raises fundamental questions about the intellectual foundations of the global financial crisis."--Publisher's abstract.